Concepciones de un grupo de docentes de secundaria sobre la enseñanza del pensamiento crítico en temas controversiales del área de ciencias sociales - Sotelo Munayco, María Lucero (2024)
Critical thinking is essential for facing the demands of a complex world, as it enables us to discern between truthful and biased information and to build knowledge autonomously. This fosters better citizenship and a critical analysis of reality, including controversial issues. Since it is an important educational goal, the aim of this study was to analyze the perceptions of a group of secondary school teachers from a public school in Lima regarding the teaching of critical thinking in the context of controversial issues. A semi-structured interview was conducted, and the participants joined virtually. The results indicate that teachers are motivated to teach critical thinking, but they lack sufficient theoretical and practical tools to do so effectively. These findings are discussed in terms of their relevance for educational processes.